Resource partitioning between low-density and high-density grazers : sable antelope, zebra and buffalo - Macandza, Valerio Antonio (My University, 2010)
The issue of how the spatial scale and other aspects of food resources and habitat conditions may enable several species of grazing herbivores to coexist while using the same grass resources in the same region is of fundamental importance in ecology and management of herbivore communities. With this project I aimed at improving the understanding of the ecology of the tall-grass grazers assemblage, particularly how the spatial scale of resource use influenced resource partitioning between grazers that attain different regional density in the same region. Based on theories of patterns of species abundance, body size, feeding specialization and competition, I predicted that at all spatial scales the low density, smaller, resource specialist sable would be more narrowly selective for resources than the high density and generalist grazers buffalo and zebra, which I expected to be more broadly tolerant to resources at different spatial scales. I found that the grass species most preferred by sable were also preferred by the abundant species, but buffalo and zebra grazed a wider range of grass species than sable. Sable were narrowly selective for green grass whereas buffalo and zebra grazed grass within a wider range of phenological stages, including completely brown grass. The three grazers overlapped in habitat features prevailing in foraging areas and, contradicting expectations, the breadth of habitat features in areas used did not differ among grazers. The low density sable used resources that occurred in restricted areas of the landscape during periods of food abundance, but the resources required became sparser as the dry season progressed prompting sable to move notably more widely during the late dry season. Buffalo and zebra used space more evenly suggesting that resources supporting these high density grazers were abundant and widely distributed in the landscape yearround. The sections of the landscape supporting the low density sable were distinct from areas frequently used by high density grazers. Overall, results showed that resource partitioning occurred through spatial separation of core grazing areas, despite overlaps at lower spatial levels of resource use. The narrow tolerance of resources by sable at the grass species and grass features level suggests that the dry season is a more stressful period to sable than to more common grazers due to a progressive decrease in the availability of resources favoured by sable. This could contribute to explaining why sable occur in low density as well as the decline and the lack of recovery by the population.